2014
DOI: 10.1007/s10753-014-0039-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Lung-Protective Ventilatory Strategy on Systemic and Pulmonary Inflammatory Responses During Laparoscopic Surgery: Is It Really Helpful?

Abstract: Laparoscopic surgery is performed by carbon dioxide (CO2) insufflation, but this may induce stress responses. The aim of this study is to compare the level of inflammatory mediators in patients receiving low tidal volume (VT) versus traditional VT during gynecological laparoscopic surgery. Forty American Society of Anesthesiologists (ASA) physical status 1 and 2 subjects older than 18 years old undergoing laparoscopic gynecological surgery were included. Systemic inflammatory response was assessed with serum I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
1
5
0
2
Order By: Relevance
“…The inflammatory factors increased slightly, and there was no significant difference between the two groups. The results of the present study are similar to those of previous studies with regard to inflammatory mediators (42,43) and PLOS (44).…”
Section: Discussionsupporting
confidence: 92%
“…The inflammatory factors increased slightly, and there was no significant difference between the two groups. The results of the present study are similar to those of previous studies with regard to inflammatory mediators (42,43) and PLOS (44).…”
Section: Discussionsupporting
confidence: 92%
“…A recent study demonstrated that there was no obvious evidence supporting atelectasis as the main cause of early postoperative fever [28]. Instead, surgical stress and the accompanying increase in circulating inflammatory cytokines may be associated with early postoperative fever [28,31]. The different ventilator modes may have affected surgical stress and the inflammatory response, but this issue was beyond the scope of the current study.…”
Section: Discussionmentioning
confidence: 76%
“…The role of lung‐protective ventilation in laparoscopic surgery is less clear. Initial studies have not shown a difference in inflammatory markers dependent on ventilation technique . The effect of different levels of PEEP on PPCs in obese patients is currently being explored in the PROBESE study (NCT02148692), in lung surgery in PROTHOR (NCT02963025) and in robotic surgery with high levels of head down tilt in AVATaR (NCT02989415).…”
Section: Are Lung‐protective Techniques Relevant To Patients Without mentioning
confidence: 99%